Physicochemical, Structural, and Biological Properties of Polysaccharides from Dandelion - Guo, Huijing (Molecules, 2019)
The edible and medicinal perennial herb dandelion is known to have antitumor, antioxidant, and anticomplement properties. However, the structural characterization and biological effects of its polysaccharides are not well understood. Here, we aimed to extract and investigate a novel polysaccharide from dandelion. A water-soluble polysaccharide, PD1-1, was successfully obtained from dandelion through ultrasonic-assisted extraction and purification using diethylaminoethyl (DEAE)–Sepharose fast flow and Sephadex G-75 columns. The results showed that PD1-1 is an inulin-type polysaccharide with a molecular weight of 2.6 kDa and is composed of glucose (52.39%), and mannose (45.41%). Glycosidic linkage analysis demonstrated that PD1-1 contains terminal α-d-Man/Glcp-(1→ and →1)-β-d-Man/Glcf-(2→ glycosidic linkage conformations. A physicochemical analysis indicated that PD1-1 has a triple helix structure and exhibits important properties, including good swelling, water-holding, and oil-holding capacities. Furthermore, PD1-1 showed good antioxidant activities in DPPH and hydroxyl free radical scavenging abilities, with IC(50) values of 0.23 mg/mL and 0.25 mg/mL, respectively, and good hypoglycemic activities in α-amylase and α-glucosidase inhibition, with IC(50) values of 0.53 mg/mL and 0.40 mg/mL, respectively, in a concentration-dependent manner. Results suggest that PD1-1 possesses efficacious antioxidant and hypoglycemic properties and has potential applications as a functional food ingredient.